Legal foundations of crowdlending: from mutual agreement to lending via online platforms - Marina Rojo Gallego-Burín; Araceli Rojo Gallego-Burín (Revista Iberoamericana de Estudios de Desarrollo)
Technological innovation in the field of finance requires in-depth study of both technology and law. To contribute to this field, this paper proposes to analyse crowdlending, a procedure that allows the conclusion of loan agreements in which intermediaries disappear and online platforms participate. This procedure presents numerous legal challenges to which we must respond, and response requires analysing our legal foundations. As everythi ng has its precedent, meeting the legal challenges of regulating crowdlending requires study of its antecedents and, thus, analysis of the loan agreement. We have found as a legal precedent the contract of mutual (mutuum) of the Roman Law because this system configures the loan contract also without intermediaries. We studied it to check the problems it raised and what were its solutions. This is the starting point to face the analysis of crowdlending.